Transitivity model applied to the management of mental health community - Narváez, Jonnathan (Universidad y Salud, 2014)
Introduction: The transitivity model is a paradigm of social intervention based on self-organizing community status as guarantor of its own processes. Objective: To validate the postulates of transitivity model in the revitalization of community clinical scenarios for the management of mental health in the municipality of San Lorenzo - Nariño in 2013. Materials and methods: The study was developed from the qualitative paradigm through participatory action research. Results: The transitivity model promotes transit homeostasis - accommodation, potentiating the participatory dimension of the subject in the transformation of social structures from the creation of public policies that ensure the planning and implementation of scenarios around participatory revitalization of community mental health in the Municipality. Conclusion: The results of the study highlight the importance of transitivity model in managing community mental health by providing intervention tools that enable engaging communities as agents of transformation of previous states of accommodation to final states of homeostasis that guarantee mental health and collective welfare of their communities.